On the Ciidae (Coleoptera) described by Michio Chûjô deposited in the Natural History Museum of Denmark - Souza-Gonçalves, Igor; Lopes-Andrade, Cristiano (Zootaxa, 2024)
The Japanese entomologist Michio Chûjô described five Ciidae species collected during the Danish “Noona Dan” Expedition in 1961–62 to the southern Philippines and the Bismarck Archipelago, Papua New Guinea. We had access to images of their holotypes deposited in the Natural History Museum of Denmark and concluded that some taxonomic changes are necessary to better position them within the currently recognized Ciidae genera. The following new combinations are proposed: Ditrichocis mussauense (Chûjô, 1966) comb. nov., Neoennearthron mindanaonus (Chûjô, 1966) comb. nov., Nipponocis palawanus (Chûjô, 1966) comb. nov., and Paratrichapus bismarckensis (Chûjô, 1966) comb. nov.. Images of all holotypes are provided, as far as comments justifying the four new combinations and the retention of Octotemnus palawanus Chûjô, 1966 in the genus.